Race and perceived racism, education, and hypertension among Brazilian civil servants: the Pró-Saúde Study - Eduardo Faerstein; Dóra Chor; Guilherme Loureiro Werneck; Claudia de Souza Lopes; George Kaplan (Revista Brasileira de Epidemiologia, 2014)
INTRODUCTION: Brazil has the largest population of African descendants outside Africa. OBJECTIVE: Mindful of the imprint of slavery on their contemporary social position, we investigated the relationship of perceived racism to hypertension. METHODS: We analyzed data (1999 - 2001) from 3,056 civil servants (mean age 42 years; 56% females) at university campuses in Rio participating in the longitudinal Pró-Saúde Study. RESULTS: Cases of prevalent hypertension had measured blood pressure equal to or greater than 140/90 mmHg or used antihypertensive medication. Self-administered questionnaires assessed participants' perceived history of lifetime discrimination (due to race, gender, socioeconomic position, and other attributes) at work and school, neighborhood, public places, and in contact with the police. Participants used 41 terms as responses to an open-ended question on racial self-identification; for these analyses, 48% were classified as afrodescendants. Racial discrimination in at least one setting was reported by 14% of afrodescendants. Compared to whites, the age- and gender-adjusted prevalence of hypertension was higher for afrodescendants with history of self-perceived racism (prevalence ratio - PR = 2.1; 95%CI 1.5 - 3.0) than for those with no such history (PR = 1.5; 95%CI 1.2 - 1.8). Comparing the former to whites, the adjusted association with hypertension was stronger for those with elementary education (PR = 3.0; 95%CI 1.3 - 6.7) than for those with a college degree (PR = 1.7; 95%CI 1.0 - 3.1). CONCLUSION: Racism may increase the risk of hypertension of afrodescendants in Brazil, and socioeconomic disadvantage - also influenced by societal racism - may further potentiate this increased risk.